2013
DOI: 10.18561/2179-5746/biotaamazonia.v3n2p11-22
|View full text |Cite
|
Sign up to set email alerts
|

Biologia Populacional de Macrobrachium jelskii (MIERS, 1778) (Crustacea, Decapoda, Palaemonidae) em uma Planície Inundável na Amazônia Oriental, Brasil

Abstract: RESUMO. A biologia populacional de M. jelskii foi investigada com ênfase na distribuição de frequência de comprimento, razão sexual, período reprodutivo e relação peso comprimento. A amostragem foi realizada durante o período de abril/2008 a maio/2009 junto às macrófitas, em um transecto de 50 m. As coletas foram obtidas com peneiras de 55 cm de diâmetro e malha de 2 mm, a cada 2 m, totalizando 25 amostras em todo o período de estudo. No laboratório, os exemplares de M. jelskii foram medidos, pesados, sexados … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 8 publications
1
7
0
2
Order By: Relevance
“…Gamba (1997) and Barros-Alves et al (2012) found female biased sex ratios in populations from Venezuela, and from state of Minas Gerais, Brazil, respectively. On the other hand, Lima et al (2013) and Mossolin et al (2013) found no statistical difference in the sex ratio of populations from eastern Amazonia and from São Paulo State, respectively. Finally, Soares et al (2015), studying a population from the São Francisco River, found a female biased sex ratio in lentic environments and the opposite condition in lotic ones.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…Gamba (1997) and Barros-Alves et al (2012) found female biased sex ratios in populations from Venezuela, and from state of Minas Gerais, Brazil, respectively. On the other hand, Lima et al (2013) and Mossolin et al (2013) found no statistical difference in the sex ratio of populations from eastern Amazonia and from São Paulo State, respectively. Finally, Soares et al (2015), studying a population from the São Francisco River, found a female biased sex ratio in lentic environments and the opposite condition in lotic ones.…”
Section: Discussionmentioning
confidence: 72%
“…Specifically in the case of M. jelskii, rainfall and water temperature play key roles in establishing the reproductive period, as several authors have noted the intensification of the reproductive activity during the warmer and humid months (Gamba, 1997;Lima et al, 2013;Mossolin et al, 2013;Soares et al, 2015;present study).…”
Section: Population Biology Of Macrobrachium Jelskii From Bahiamentioning
confidence: 83%
See 2 more Smart Citations
“…Sin embargo, esto no concuerda con lo señalado por Pereira (1986) en corrientes venezolanas, quien registró machos con 38,6 mm (LT) y 10,3 mm (LCF), y hembras con 35 mm (LT) y 9 mm (LCF). En otras especies como Palaemon pandaliformis, P. northropi Rankin, 1898, M. amazonicum, M. potiuna y M. jelskii Miers, 1877 las hembras son más pequeñas que los machos (Anger y Moreira 1998, Maciel y Valenti 2009, Lima et al 2013, De Melo y Masurani 2017. Se han planteado algunas hipótesis que explican la variación del tamaño entre sexos en Palaemonidae; una explica que los machos son mucho más grandes porque compiten por aparearse con las hembras e invierten mucha energía para el crecimiento corporal y la adquisición de quelípedos robustos (Correa y Thiel 2003, Bauer 2004, y otra afirma que los machos pequeños y ágiles tienen mayor oportunidad de aparearse varias veces con diferentes hembras y no gastan energía protegiendo territorios (Bauer 2004) pero sí en la producción de esperma (Paschoal et al 2013).…”
Section: Discussionunclassified